2021
DOI: 10.3389/fonc.2021.658829
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Intra-Peritoneal Drainage After Pancreatic Resection: An Updated Meta-Analysis

Abstract: IntroductionProphylactic intra-peritoneal drainage has been considered to be an effective measure to reduce postoperative complications after pancreatectomy. However, routinely placed drainage during abdominal surgery may be unnecessary or even harmful to some patients, due to the possibility of increasing complications. And there is still controversy about the prophylactic intra-peritoneal drainage after pancreatectomy. This meta-analysis aimed to analyze the incidence of complications after either pancreatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…However, in our present analysis based on 1049 patients, we found that PD did not show any advantage over ND in patients undergoing total gastrectomy. Unexpectedly, several recent meta-analyses demonstrated that even pancreaticoduodenectomy and major liver resection can safely avoid abdominal drainage, which indicated that PD is not a substitute for a meticulous surgical procedure in complex operations [8,45]. In view of this, avoiding routine drainage should also be recommended during total gastrectomy.…”
Section: Discussionmentioning
confidence: 99%
“…However, in our present analysis based on 1049 patients, we found that PD did not show any advantage over ND in patients undergoing total gastrectomy. Unexpectedly, several recent meta-analyses demonstrated that even pancreaticoduodenectomy and major liver resection can safely avoid abdominal drainage, which indicated that PD is not a substitute for a meticulous surgical procedure in complex operations [8,45]. In view of this, avoiding routine drainage should also be recommended during total gastrectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Drainage tube-related problems comprising 35.9% of patients in the discharged group ( n = 39) implied that this problem had relatively low acuity. The role of the routine intraoperative placement of drainage tubes during PD remains controversial [ 26 , 27 ]. Several meta-analysis studies have demonstrated comparable results between patients with or without routine drainage tube placement after PD, particularly for those at low risk of POPF [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The role of the routine intraoperative placement of drainage tubes during PD remains controversial [ 26 , 27 ]. Several meta-analysis studies have demonstrated comparable results between patients with or without routine drainage tube placement after PD, particularly for those at low risk of POPF [ 27 , 28 ]. Although it is not feasible to conclude the necessity of drainage tube placement, these results exhibited a notion of avoiding unnecessary drainage tube placement to avert postoperative complications [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Conlon et al (8) performed the first randomized controlled trial (RCT) to demonstrate that the placement of drainage after pancreatic resection failed to reduce postoperative complications, but increased the incidences of intra-abdominal collections and infection. Subsequently, multiple RCTs and metaanalysis proved the safety of omission of drainage after pancreatic resection (9)(10)(11)(12)(13). However, one RCT was stopped because of the significantly increased mortality from 3% to 12% for patients undergoing PD without the placement of intraperitoneal drainage (14).…”
Section: Introductionmentioning
confidence: 99%